2018
DOI: 10.3389/fpsyt.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Network Efficiency of Functional Brain Networks in Primary Insomnia Patients

Abstract: Accumulating evidence from neuroimaging studies suggests that primary insomnia (PI) affects interregional neural coordination of multiple interacting functional brain networks. However, a complete understanding of the whole-brain network organization from a system-level perspective in PI is still lacking. To this end, we investigated in topological organization changes in brain functional networks in PI. 36 PI patients and 38 age-, sex-, and education-matched healthy controls were recruited. All participants u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 86 publications
3
41
0
Order By: Relevance
“…In our study, anatomical topology analysis revealed that the two study groups had characteristic small-world organization, which was consistent with the finding of previous studies ( Lu et al, 2017b ; Ma et al, 2018 ). Eg and Eloc were used as measures of functional integration and segregation, respectively ( Rubinov and Sporns, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, anatomical topology analysis revealed that the two study groups had characteristic small-world organization, which was consistent with the finding of previous studies ( Lu et al, 2017b ; Ma et al, 2018 ). Eg and Eloc were used as measures of functional integration and segregation, respectively ( Rubinov and Sporns, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Graph analyses revealed diurnal differences in the CRB associated with higher measures of network centrality such as nodal efficiency and degree and betweenness centrality in the evening compared with the morning. These results indicate the high ability of bilateral Crus I and II but also left lobules VIIB, VIII, and X of the cerebellar hemisphere to transmit the information to other regions included in the CRB [ 95 ]. Dynamic interaction is related to greater efficiency and thereby better functioning of the whole cerebellum, which, apart from basic motor control such as voluntary limb movements, balance, and maintaining posture [ 96 ], is associated with the visual attention process and working memory [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…For a graph (G), GE is defined as the average of the inverse of the shortest path length from each node to all other nodes [ 62 , 63 ] which is mathematically expressed by: where d(i,j) is the shortest path length between node i and node j in graph G and is calculated as the smallest sum of edge/connections lengths throughout all possible paths from node i and node j. The length of a connection or edge was considered as the reciprocal of the connection weight (here, their PLV or FC), under the assumption that the distance between two nodes is inversely proportional to their FC [ 64 ]. Local efficiency (LE), which for a node is defined as the GE of the node, calculated in the subgraph created by its neighbors.…”
Section: Methodsmentioning
confidence: 99%
“…Taking both measures (LE and GE) into consideration, a regular network or lattice is defined as having high LE and low GE, a random network has low LE and high GE, and a small-world (SW) network would lie somewhere between a regular and random network, with a high LE and GE. To check whether a real network has a small-world structure, one of the proposed methods is to normalize LE and GE in the real network, in relation to those computed in matched random networks e.g., dividing LE and GE by the corresponding mean [LE(r) or GE(r)] obtained from 100 random networks that preserved the same number of nodes, connections, and degree distributions as the real brain networks [ 64 , 65 , 66 ]. In this way, a SW network would be characterized by having LE > LE(r), and a comparable GE ~ GE(r) or having the normalized versions NLE = LE/LE(r) > 1 and NGE = GE/GE(r) ~ 1.…”
Section: Methodsmentioning
confidence: 99%